Association of food neophobia and food disgust with the willingness, benefits, and risks of insect food consumption among Chinese university students - Tian, Hua; Chen, Jie (Frontiers in Nutrition, 2025)
IntroductionEdible insects with high protein content are sufficient to meet the growing global demand for protein. However, some individuals have negative psychological reactions such as phobia and disgust toward insect foods; therefore, the large-scale promotion of insect foods has progressed slowly. This study investigated the impact of food neophobia and food disgust on the willingness, benefits, and risks of insect food consumption among Chinese university students.MethodsIn 2023, 560 university students aged 18–25 years were recruited to fill an online questionnaire. The data were analyzed using a Mann–Whitney U test.ResultsMost university students were unfamiliar and unwilling to consume insect foods, with higher levels of food neophobia and disgust indicating greater unwillingness to consume insect foods. Regardless of food neophobia and disgust levels, both groups agreed on the benefits of consuming insect foods and believed that consuming insect foods carried high risks.ConclusionThese findings underscored the significance of promoting and enhancing positive cognitions surrounding insect foods, and eliminating negative stereotypes about insect foods, especially those university students with high food neophobia or disgust. In addition, the findings provide reference for studying the psychological mechanism of insect food consumption and guiding young people to consume insect foods.